2006
DOI: 10.1007/s10755-005-9004-2
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Study Strategies as a Function of Testing: An Investigation into Metacognitive Self-Regulation

Abstract: We conducted the present study to investigate whether college students adjust their study strategies to meet the cognitive demands of testing, a metacognitive self-regulatory skill. Participants were randomly assigned to one of the two testing conditions. In one condition we told participants to study for a test that required deeplevel cognitive processing and in the other to study for a test that required surfacelevel cognitive processing. Results suggested that college students adjust their study strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 30 publications
0
34
0
4
Order By: Relevance
“…Much less literature addresses the mechanism of this impact; most of this is fragmented (reviewed in 16 ). There have been few attempts to propose theoretical models to explain how pre‐assessment learning effects come about 12,17–21 . However, none of these models has been validated.…”
Section: Introductionmentioning
confidence: 99%
“…Much less literature addresses the mechanism of this impact; most of this is fragmented (reviewed in 16 ). There have been few attempts to propose theoretical models to explain how pre‐assessment learning effects come about 12,17–21 . However, none of these models has been validated.…”
Section: Introductionmentioning
confidence: 99%
“…Araştırmacılar, öğretmenlerin üstbilişsel farkındalık ve becerilerini geliştirmek için, kayıt tutma, yansıtıcı düşünme, problem temelli öğrenme, hedef koyma, işbirlikçi çalışma grupları oluşturma, öz değerlendirme gibi pek çok teknik ve stratejiler belirlemişlerdir (Akın ve Abacı, 2001;Case ve Gunstone, 2002;De Backer, Keer ve Valcke, 2012;Papinczak, Young, Grooves ve Haynes, 2008;Ross, Green, Salisbury-Glennon & Tollefson, 2006;Simons, 1994;Zimmerman, 1989). 233 Simons (1994), yükseköğretimde öğretmenlerin üstbilişsel gelişimlerini desteklemeye yönelik ilkeler önermiştir.…”
unclassified
“…In the existing literature, scholars have consistently shown that SRL helps high achievers reach their potential (Risemberg and Zimmerman 1992) and makes a difference between failure and success for low achievers (Borkowski and Thorpe 1994). In addition, Ross et al (2006) and Zimmerman (1986) also express that the research demonstrates that SRL is a significant predictor of achievement based on college students' assignment to developmental/remedial or regular college admission (Ley and Young 1998) and grade point average (Van Zile-Tamsen and Livingston 1999).…”
Section: Self-regulated Learningmentioning
confidence: 99%